Clinical Utility of Germline Genetic Testing in Japanese Men Undergoing Prostate Biopsy. Issue 1 (9th January 2022) - Akamatsu, Shusuke; Terada, Naoki; Takata, Ryo; Kinoshita, Hidefumi; Shimatani, Kimihiro; Momozawa, Yukihide; Yamamoto, Michio; Tada, Harue; Kawamorita, Naoki; Narita, Shintaro; Kato, Takuma; Nitta, Masahiro; et al.
Abstract: Background: Multiple common variants and also rare variants in monogenic risk genes such as BRCA2 and HOXB13 have been reported to be associated with risk of prostate cancer (PCa); however, the clinical setting in which germline genetic testing could be used for PCa diagnosis remains obscure. Herein, we tested the clinical utility of a 16 common variant–based polygenic risk score (PRS) that has been developed previously for Japanese men and also evaluated the frequency of PCa-associated rare variants in a prospective cohort of Japanese men undergoing prostate biopsy. Methods: A total of 1336 patients undergoing first prostate biopsy were included. PRS was calculated based on the genotype of 16 common variants, and sequencing of 8 prostate cancer–associated genes was performed by multiplex polymerase chain reaction based target sequencing. PRS was combined with clinical factors in logistic regression models to assess whether addition of PRS improves the prediction of biopsy positivity. Results: The top PRS decile was associated with an odds ratio of 4.10 (95% confidence interval = 2.46 to 6.86) with reference to the patients at average risk, and the estimated lifetime absolute risk approached 20%. Among the patients with prostate specific antigen 2-10 ng/mL who had prebiopsy magnetic resonance imaging, high PRS had an equivalent impact on biopsy positivity as a positive magnetic resonance imaging finding. Rare variants were detected in 19 (2.37%) and 7 (1.31%) patients with positive and negative biopsies, respectively, with BRCA2 variants being the most prevalent. There was no association between PRS and high-risk rare variants. Conclusions: Germline genetic testing could be clinically useful in both pre- and post-PSA screening settings.